Counselling Muslims: A Culture-Infused Antidiscriminatory Approach - Qasqas, Mahdi J.; Jerry, Paul (Canadian Journal of Counselling and Psychotherapy, 2014)
There are approximately 1.57 billion Muslims in the world, with approximately 940,000 living in Canada. Furthermore, the population of Muslims living in Canada is expected to grow to about 2.7 million by 2030. Despite the high numbers and anticipated growth of this population, there still exists a dearth of research on the worldviews and intracultural differences of Muslims. Understanding the worldviews and intracultural differences of Muslims is essential if counsellors and psychologists intend to practice in an antidiscriminatory and culturally competent manner, especially given the increased awareness of the psychosocial needs of Muslims in the decade or so that followed the 9/11 attacks. However, if counsellors and psychologists are unwilling to challenge existing biases and stereotypes in their own minds, or are unaware of how to do it, then they may unintentionally engage in unethical prejudicial and discriminatory practices. The authors aim to encourage counsellors and psychologists to apply an aspirational level of ethical practice when working with nondominant populations in general and Muslims in particular. In the article, ethical obligations are mentioned first, followed by an in-depth exploration of the major sources of discrimination. The authors then discuss several theoretical models of the development of bias. Subsequently an exploration into the use of Arthur and Collins’ culture-infused counselling framework for working with Muslims in Canada is put forth. The example of Muslim women wearing the religious veil known as hijab is used to highlight these points and allows readers to explore their own level of cultural competency in working with Muslim clients.